Negotiating Islamic Hegemony: A Case Study of Muslim LGBT in East Java, Indonesia - Wijianto, Agung; Wahid, Farah Kholida (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research set out to investigate how Islamic hegemonic processes disseminate in society. It also tried to examine how LGBT individuals negotiate the tension and navigate their behaviors of being Muslim and LGBT. In Indonesia, being a Muslim and LGBT was viewed as irreconcilable by the general public. Despite that, some people identified as both Muslim and LGBT. This posed a tension that needed to be addressed. The research distributed online forms across several social media to find willing participants. The online forms yielded seven different responses from people who identified as Muslims and LGBT, three of whom were willing to participate in follow-up interviews. The willing participants were then personally interviewed in informal settings using Zoom video calls due to the COVID-19 pandemic. The interviews were semi-structured, and they were carried out over the course of four weeks. The research drew on concepts such as cultural hegemony and ideological state apparatuses as conceptual frameworks to guide the research and the interviews. The findings suggest that family and education are the two most influential hegemonic instruments in instilling Islamic hegemonic values in the participants. The research also finds that the respondents perform unique distinct negotiation strategies according to their personal beliefs and values on social and spiritual levels.